FACILITATION IS A PERSON-ORIENTED APPROACH IN MODERN PSYCHOLOGICAL EDUCATION - Mamanova Dinora Olimjonovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article examines the concept of a "pedagogue-facilitator" and its importance in modern education. The article analyzes K. Rogers' person-centered education concept, the functions of a facilitator-teacher, as well as the factors of creating a trusting environment in the facilitation process. The article also discusses the role of facilitation psychology in modern education and its contribution to the self-development of teachers and students.